2012
DOI: 10.1007/s00262-012-1294-5
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils and granulocytic myeloid-derived suppressor cells: immunophenotyping, cell biology and clinical relevance in human oncology

Abstract: Accumulating evidence indicates that myeloid cells are critically involved in the pathophysiology of human cancers. In contrast to the well-characterized tumor-associated macrophages, the significance of granulocytes in cancer has only recently begun to emerge. A number of studies found increased numbers of neutrophil granulocytes and granulocytic myeloid-derived suppressor cells (GrMDSCs) both in the peripheral blood and in the tumor tissues of patients with different types of cancer. Most importantly, granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
309
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 343 publications
(314 citation statements)
references
References 92 publications
2
309
0
3
Order By: Relevance
“…30,31 Nevertheless, neutrophils represent an independent prognostic marker in a broad variety of neoplasias. For instance, a high number of intratumoral neutrophils in localized 32 as well as metastatic 32 renal cell carcinoma, correlates with a negative prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Nevertheless, neutrophils represent an independent prognostic marker in a broad variety of neoplasias. For instance, a high number of intratumoral neutrophils in localized 32 as well as metastatic 32 renal cell carcinoma, correlates with a negative prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…When viewed in combination, these markers were suggestive of a granulocytic/neutrophilic MDSC subtype (PMN-MDSCs). 18,29 Percentages of monocytic MDSCs in peripheral blood were substantially lower (monocytic MDSCs mean 0.12% before ECP) compared with PMN-MDSCs (mean 6% before ECP) in our patient cohorts and did not change significantly upon ECP treatment (Supplementary Figure 2). We therefore systematically followed up on the observation that ECP Table 1.…”
Section: Ecp Rapidly Increases Neutrophilic Mdscs In Gvhd Patientsmentioning
confidence: 93%
“…Several factors have been involved into the generation and functionality of MDSCs, particularly arginase, Signal Transducer and Activator of Transcription 3 (STAT3), indoleamine 2,3-dioxygenase (IDO), reactive oxygen species and others. 18,19 As previous studies found that ECP enhances arginase I mRNA expression and enzyme activity in GvHD patients, 31 we focused on this pathway in our study. Our analyses demonstrated that ECP treatment increased arginase I activity both extracellularly in serum and intracellularly in the PMN-MDSC-containing PBMC fraction in GvHD patients, with PMN-MDSCs showing tendentially higher arginase I activity compared with autologous PBMCs (Figure 2c and Supplementary Figure 7).…”
Section: Neutrophilic Mdscs Functionally Suppress T-cell Responsesmentioning
confidence: 99%
See 2 more Smart Citations